PENERAPAN MEDIA GAME EDUKASI BERBASIS SMARTBORT DALAM PEMBELAJARAN MENULIS AKSARA JAWA DI SMP - Prasetyo, Daniel Dwi; Alfiah, Alfiah; Sunarya, Sunarya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Javanese script as a cultural heritage is currently threatened with extinction due to the lack of interest and innovation in learning, particularly at the junior high school level. This study aims to describe the implementation of smartboard-based educational game media and examine students' responses in learning to write Javanese script in grade VII of SMP Negeri 2 Donorojo. The method used is descriptive qualitative with an implementation study design. Data were collected through post-test and questionnaire instruments from 22 students and analyzed using the percentage technique based on Riduwan's (2013) assessment classification. The results show that the students' average post-test score reached 84.90 with a classical completeness rate of 100%, categorized as